A depositional model for spherulitic carbonates associated with alkaline, volcanic lakes. (September 2017) - Mercedes-Martín, Ramon; Brasier, Alexander T.; Rogerson, Mike; Reijmer, John J.G.; Vonhof, Hubert; Pedley, Martyn
Abstract: The South Atlantic Aptian 'Pre-salt' reservoirs are formed by a combination of spherulitic carbonates and Mg-rich clays accumulated in volcanic alkaline lake settings with exotic chemistries. So far, outcrop analogues characterised by metre-thick successions deposited in lacustrine scenarios are elusive so disentangling the genesis of spherulitic carbonates represents a major scientific challenge with business impact. In particular the controls on spatial distribution and the environment of spherulitic facies formation remain poorly constrained, little studied, and hotly debated. To shed light on this conundrum, a spherulitic carbonate-rich, alkaline volcanic lacustrine succession has been analysed at outcrop scale: the Carboniferous East Kirkton Limestone (Scotland). Despite clays being very scarce and limited to layers of amorphous Mg-Si minerals, a diverse array of spherulitic calcitic components were formed, including coated grains, crusts, and build-ups. This setting enables the mechanisms of spherulitic calcite development and the patterns of sediment accumulation to be explored in a geobiological and hydrochemical scenario similar to the 'Pre-Salt' subsurface occurrences but divorced from clay influence. The integration of logs, borehole data, outcrop photomosaics and petrographic observations collectively allowed the reconstruction of a depositional model for the East Kirkton lacustrine succession. In this model, calcite spherule nucleation took place at the sediment-water interface in the littoral zone, driven by the co-occurrence of 1) high alkalinity, 2) Ca-Mg rich hydrochemistry, and 3) microbial-derived colloidal exopolymeric substances. These environmental conditions permitted the coeval development of spherulitic cementstone build-ups and spherulitic grainstone-packstone within the wave-agitated zone, and the accumulation of floatstones and laminites of spherulitic grains in deeper lake regions by means of downslope reworking. This model is consistent with the previously documented microbial bloom occurrences and highlights the need to better understand the complex 'microbe-solution' interactions before any reliable facies model is envisaged. Graphical abstract: Highlights: Spherulitic calcite components formed in a clay-poor, volcanic and alkaline lake. The spherulitic carbonate factory was located in the littoral lake region. Microbe-derived exopolymeric substances likely triggered spherulitic fabrics. Spherulitic cementstone and spherulitic grainstone-packstone coexisted in the littoral zone. Downslope resedimentation of spherulites produced spherulitic floatstone textures.